2015
DOI: 10.1007/s12560-014-9179-8
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Human Adenoviruses in Water Saturated Laboratory Columns

Abstract: Groundwater may be contaminated with infective human enteric viruses from various wastewater discharges, sanitary landfills, septic tanks, agricultural practices, and artificial groundwater recharge. Coliphages have been widely used as surrogates of enteric viruses, because they share many fundamental properties and features. Although a large number of studies focusing on various factors (i.e. pore water solution chemistry, fluid velocity, moisture content, temperature, and grain size) that affect biocolloid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
2
15
0
Order By: Relevance
“…To our knowledge, to date, there has been no study on human adenovirus transport in saturated porous media in the presence of clay colloids and TiO 2 NPs. Certainly, this work is a substantial extension of the work conducted by Kokkinos et al (2015), who studied the effect of flow velocity on the transport of human adenoviruses. Column experiments were conducted using glass beads as the column packing material in order to eliminate possible experimental difficulties associated with real soil, which may provide numerous uncertainties that can considerably complicate the analysis of the experimental data.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…To our knowledge, to date, there has been no study on human adenovirus transport in saturated porous media in the presence of clay colloids and TiO 2 NPs. Certainly, this work is a substantial extension of the work conducted by Kokkinos et al (2015), who studied the effect of flow velocity on the transport of human adenoviruses. Column experiments were conducted using glass beads as the column packing material in order to eliminate possible experimental difficulties associated with real soil, which may provide numerous uncertainties that can considerably complicate the analysis of the experimental data.…”
Section: Introductionmentioning
confidence: 87%
“…Fig. 2 shows the normalized breakthrough data for the cotransport of hAdV35 with KGa-1b, STx-1b and TiO 2 NPs, at three flow rates (2.5, 1.5, 0.8 mL/min), together with the breakthrough data for the transport of hAdV35, which were collected by Kokkinos et al (2015). Note that the total virus concentrations represent the sum of suspended viruses and viruses sorbed onto suspended particles (C Total-v = C v + C vp ).…”
Section: Analysis Of Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Three recent studies by independent research groups (Shi et al 2012;Pang et al 2014;Wong et al 2014), applied qPCR to column filtration experiments and they all found mobility of human adenovirus (HAdV, the most prevalent enteric virus in water environments) (Wong et al 2012a) to be much lower than MS2 (the most frequently used bacteriophage in virus transport studies) (Jin and Flury 2002;Wong et al 2014) in sand media. Another study also found mass recovery of HAdV from glass beads column effluents lower than coliphage reported in previous studies (Kokkinos et al 2015). One study, however, reported higher retention of MS2 than HAdV in fine granular limestone aquifer material; and suggested that PRD1 was a better transport indicator than MS2 for HAdV in this type of media (Stevenson et al 2015).…”
Section: Needs For Understanding the Transport Behavior Of Enteric VImentioning
confidence: 77%